Pemberdayaan UMKM melalui Sosialisasi Pembukuan Sederhana Berbasis Microsoft Excel di Desa Ngrapah, Kecamatan Banyubiru, Kabupaten Semarang - Diva Ayu Imanda Sari; Tri Nurul Khomidah; Eiffeliena Nur A.F.P; Ibnu Muttaqin; Lindu Aji Santoso (Yayasan Sumber Daya Manusia Cerdas, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the local economy, including in Ngrapah Village, Banyubiru District, Semarang Regency. However, most MSME actors still face limitations in financial recording and bookkeeping, particularly in utilizing simple digital technologies such as Microsoft Excel. This community service activity aimed to improve the understanding and skills of MSME actors in preparing simple bookkeeping using Microsoft Excel to support more systematic and efficient financial management. The activity was conducted using a participatory approach through socialization sessions, hands-on practice, discussions, and individual mentoring supported by a simple bookkeeping module. The participants consisted of 30 individuals in Ngrapah Village. Evaluation was carried out using a pre-test and post-test approach. The results showed a significant improvement in participants’ understanding. Before the activity, 100% of participants did not understand business bookkeeping, whereas after the activity, 96.7% became highly knowledgeable and 3.3% were knowledgeable. In addition, 93.3% of participants demonstrated a high level of understanding in using Microsoft Excel for financial recording, and 90% stated that the activity was highly beneficial for their businesses. These findings indicate that socialization and mentoring on simple Excel-based bookkeeping are effective in improving accounting literacy and strengthening the financial management capacity of MSMEs in a sustainable manner.